A case of neck pain in emergency department - Krishnakumar, Ashwini kumar; K, Dhilipan; Sabarish, S; Varadharajan, Shriram; Iyer, Rajesh Shankar (Indian Journal of Case Reports, 2024)
Neck pain is a common presentation to the emergency department (ED) and a prominent source of disability in the adult population, accounting for about 10–20% of the population. Neck pain can be challenging for ED clinicians to accurately diagnose and manage. The vital role of ED remains in diagnosing the musculoskeletal red flag conditions such as cervical spine fractures or dislocations, radiculopathies, and disk disruptions. However, most non-traumatic causes of neck pain do not have a specific pathoanatomical etiology that can be identified on imaging to identify the cause of pain in the absence of red flags signs. In this article, we would like to discuss one such case, wherein our patient, a 49-year-old gentleman presented to our ED with neck pain which rapidly progressed to quadri paresis within a short duration of ED stay and the diagnostic hurdles faced and the outcome of the patient.